Effect of silica on the properties of cellulose acetatepolyethylene glycol membranes for reverse osmosis - Adnan, Ahmad; Sidra, Waheed; Shahzad, Maqsood Khan; Sabad, e-Gul; Muhammad, Shafiq; Muhammad, Farooq; Khairuddin, Sanaullah; Tahir, Jamil (Elsevier B.V., 2015)
In this work, a series of cellulose acetate/polyethylene glycol-600 membranes, with varying ratios were prepared by 2-stage phase inversion protocol. The permeation properties were studied by subjecting membranes in indigenously fabricated reverse osmosis plant. After optimization of different CA/PEG ratios, the membrane with highest salt rejection capacity was selected and modified with varying amount of silica. The Modified membranes were characterized for their permeation properties, hydrophilicity, compositional analysis, thermal stability, mechanical strength and morphological studies. Silica significantly influenced the permeation performance of composite membrane. The flux enhanced from 0.35 to 2.46 L/h m2 along with an 11.41% relative increase in salt rejection. The hydrophilicity was significantly enhanced by the addition of silica. In FTIR spectra, the broadening of the peak around 3500 cm− 1 and emergence of peak at 950 cm− 1 specified the incorporation of silica particles. The thermal analysis indicated the relative increase in degradation temperature (Tmax) and glass transition temperature (Tg) for CPS-5 membrane. The mechanical stability of the modified membranes, increased initially, but declined with further addition of silica. The results indicated that the incorporation of SiO2 content in the casting solution improved the fouling resistance of the membranes.